The policy response to home-grown terrorism: reconceptualising Prevent and Resilience as collective resistance - Aly, Anne (Routledge, 2013)
The policy response to home-grown terrorism focuses attention on the root causes of terrorism. Such soft approaches to countering terrorism are a necessary element of an effective and comprehensive strategy. The United Kingdom's Prevent strategy, Australia's Resilience approach, and the United State's Diminish element all share a focus on countering violent extremism on the home front through a policy approach that promotes democratic values, social harmony, and the active participation of Muslim communities. This paper argues that such responses are informed by flawed assumptions that have little or no evidentiary basis and calls for a reconceptualisation of soft counter terrorism as collective resistance against terrorism. It presents the preliminary findings of a qualitative research project that explores how a citizen-driven initiative to build a peace park on the site of the Bali 2002 terrorist bombings constructs a counter-narrative to terrorist propaganda and contributes to sustainable and long-term soft counter terrorism.